Family Income Distribution: Explanation and Policy Evaluation - Layard, Richard; Zabalza, Antoni (Journal of Political Economy, 1979)
Since individual welfare depends on family income, we ask two main questions: (1) Is family income more explicable than individual earnings? Due to assortative mating, schooling explains 20 percent of the experience-constant annual income of families, compared with under 15 percent of the experience-constant earnings of men. We explain this outcome using the model of family labor supply. We also experiment with other measures of family welfare. (2) How can policies affecting family income be evaluated? We argue that a lifetime income framework is needed here and show how different policies can be evaluated using explicit equity-efficiency tradeoffs.